GAMBARAN HASIL PEMERIKSAAN HEPATITIS B SURFACE ANTIGEN (HBsAg) PADA IBU HAMIL TRIMESTER SATU DI WILAYAH KERJA PUSKESMAS KOTA TENGAH - Ciery Marhamah Dunggio (LPPM Universitas Bina Mandiri Gorontalo, 2020)
Hepatitis B is inflammation or infection in liver cells caused by viruses and can be acute or chronic. According to WHO 2018, hepatitis B is a quite serious problem. In addition, the incidence of hepatitis B infection often occurs in pregnant women and has a great potential of contracting the baby. HBsAg examination in first trimester pregnant women is an early detection of vertical transmission hepatitis B. Based on data from Gorontalo City Health Office, in 2017-2018 there was an increase in the number of pregnant women infected with the hepatitis B virus by 15 people. Purpose of this research was to determine the description of the results of HBsAg examination in first trimester pregnant women at the Community Healt Center of Central City. This research is a descriptive qualitative research using HBsAg examination and immunochromatography methods. The population in this research were 30 samples with a total sampling technique. The results of HBsAg examination showed that in the first trimester pregnant women a positive result was infected with hepatitis B virus is 1 person with a percentage of 3.3% and a negative result of 29 people or 96.7%. Based on the results of research it can be concluded that first trimester pregnant women with negative HBsAg status more than positive ones